2020
DOI: 10.1007/s40279-020-01309-5
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Strength Training on Musculoskeletal System Health: Practical Applications for Interdisciplinary Care

Abstract: Full bibliographic details must be given when referring to, or quoting from full items including the author's name, the title of the work, publication details where relevant (place, publisher, date), pagination, and for theses or dissertations the awarding institution, the degree type awarded, and the date of the award.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 226 publications
(274 reference statements)
3
67
0
3
Order By: Relevance
“…Despite the adoption of a relatively homogeneous prescription approach, aerobic and strength training have been, for the most part, associated with benefits across a diverse range of populations (e.g., Bishop et al, 1999;Voisin et al, 2015;Flannery et al, 2019;Klil-Drori et al, 2020;Maestroni et al, 2020). On this evidence, it is assumed that a standardized, largely homogeneous exercise prescription that adopts a conventional approach is safe, efficacious, and therefore sufficient.…”
Section: Current Limitations Of Exercise Recommendations For Health Amentioning
confidence: 99%
“…Despite the adoption of a relatively homogeneous prescription approach, aerobic and strength training have been, for the most part, associated with benefits across a diverse range of populations (e.g., Bishop et al, 1999;Voisin et al, 2015;Flannery et al, 2019;Klil-Drori et al, 2020;Maestroni et al, 2020). On this evidence, it is assumed that a standardized, largely homogeneous exercise prescription that adopts a conventional approach is safe, efficacious, and therefore sufficient.…”
Section: Current Limitations Of Exercise Recommendations For Health Amentioning
confidence: 99%
“…Today, resistance training is widely used in physical exercise and rehabilitation environments for its proven benefits in reducing injury rates, improving skills and performance in specific sports [17]; in addition to that, this training modality has proven to be a powerful tool to restore health conditions, which is why the World Health Organization (WHO) has including resistance training as part of its recommendation of physical exercise for the general population, due to the evidence demonstrated in the prevention of non-communicable diseases and others [18,19]. However, to our knowledge, no information has yet been found that clearly indicates the baseline data provided by NIRS and its possible variation during muscle strength training in healthy adults, information that could improve our understanding of the mechanisms that influence physical performance and fatigue during this type of exercise, since blood flow can vary depending on the workload and metabolic demand [20], conditioning the response of this tissue to physical exercise [21].…”
Section: Introductionmentioning
confidence: 99%
“…Resistance training is the most effective non-pharmacological intervention known to increase skeletal muscle mass and improve both the capacity (strength) and rate (power) of force production by skeletal muscle. For this reason, resistance training (particularly the associated improvements in force production ability) can aid performance enhancement in various athletic disciplines (Suchomel et al, 2016), and also attenuate declines in these parameters occurring across the lifespan that can impair functional ability and increase the risk of both morbidity and mortality (Maestroni et al, 2020).…”
Section: Influence Of Cwi On Physiological Adaptations To Resistance mentioning
confidence: 99%